1982
DOI: 10.1080/03079458208436112
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxicosis produced in broiler chickens by multiple doses of either t‐2 toxin or diacetoxyscirpenol

Abstract: SUMMARYT-2 toxin, a 12, 13-epoxytrichothecene mycotoxin, was given by crop gavage to 7-day-old male broiler chickens as 14 daily doses of 1.5, 2.0, 2.5, and 3.0 mg/kg body weight/day. Diacetoxyscirpenol, also an epoxytrichothecene, was given at doses of 2.5, 3.0,and 3.5 mg/kg/day. Some chickens became dehydrated and emaciated and died. In survivors, body weight and haematocrit were reduced, the feathers were malformed, and the beak and legs were pale yellow. At necropsy, the lymphoid organs were atrophic, bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 27 publications
7
17
0
Order By: Relevance
“…This in-turn affects the transportation of lipid from the liver (Manegar et al, 2010). The increase in the gizzard weight in this study accords with Huff and Doerr (1981) who postulated that direct exposure of digestive organs to cytotoxins of aflatoxins during digestion process resulting in this response, while Hoerr et al (1982) attributed this increase in weight to irritation properties of mycotoxins by direct contact with organs of upper alimentary tract. (Kubena et al, 1990), which may be due to the results of severe inflammation and thickening of mucosal layer.…”
Section: Weights Of Some Internal Organssupporting
confidence: 73%
“…This in-turn affects the transportation of lipid from the liver (Manegar et al, 2010). The increase in the gizzard weight in this study accords with Huff and Doerr (1981) who postulated that direct exposure of digestive organs to cytotoxins of aflatoxins during digestion process resulting in this response, while Hoerr et al (1982) attributed this increase in weight to irritation properties of mycotoxins by direct contact with organs of upper alimentary tract. (Kubena et al, 1990), which may be due to the results of severe inflammation and thickening of mucosal layer.…”
Section: Weights Of Some Internal Organssupporting
confidence: 73%
“…The mycotoxins (T-2 toxin and diacetoxyscirpenol) of Fusarium sp. have a radiomimetic effect and will produce lesions in feathers as well as other organs (Wyatt et al, 1975;Hoerr et al, 1981Hoerr et al, , 1982. Lesions consist of necrosis of cells in the epidermal collar, rachis and barb ridges of the feather.…”
Section: Toxinsmentioning
confidence: 99%
“…T-2 toxin has previously been shown to reduce body weight gains of white leghorn and broiler chickens (25,70). Chi et al (7) reported that weight gain was most severely affected by T-2 toxin during the first 3 wk of their 9-wk study.…”
Section: Discussionmentioning
confidence: 97%
“…T-2 toxin has been found to produce necrosis, depletion, and atrophy of lymphoid tissue, lower Band T-cell numbers, inhibit lymphocyte transformation, decrease IgG and IgM antibody levels, and cause lymphocytolysis (12,21,23,25,27,30,31). In addition, T-2 toxin has been reported to induce apoptosis in thymus, hematopoietic tissues and HL-60 human promyelocytic leukemia cells (26,56,73).…”
mentioning
confidence: 98%